Effect of Cement Kiln Dust and Sugarcane Bagasse Ash on Black Cotton Soil to be used as Road Subgrade Material in Flexible Pavement Construction - Abdou Saidou, Aboubakar; Abongo, Kepha; M’tulatia, Mung’athia (Engineering, Technology & Applied Science Research, 2025)
Cement, lime, and Fly Ash (FA) are the major traditional soil stabilizers. Cement production contributes 0.8-0.9 tons of carbon emissions per ton of cement, while lime production generates around 1.2 tons of CO2 per ton of cement. FA is not readily available in all regions, necessitating the exploration of alternative stabilizing agents. Cement Kiln Dust (CKD) and Sugar-Cane Bagasse Ash (SCBA) are waste products from cement and sugarcane production, respectively. This study investigated the use of CKD and SCBA to stabilize black cotton soil. CKD was incorporated into the soil at 0, 2, 4, 6, 8, and 10% for standard Proctor compaction, consistency limits, Free Swell Index (FSI), Unconfined Compressive Strength (UCS), and California Bearing Ratio (CBR) testing. The optimal CKD content based on UCS and CBR was 6%, while the optimal CKD-SCBA composite was 6% CKD and 10% SCBA. The third part of the Kenyan Road Design Manual (KRDM III) categorizes subgrades by strength based on the CBR, ranging from S1 to S6. Subgrades classified as S1 exhibit the lowest strength (CBR of 2-5%), while S6 denotes the highest strength (CBR of 30% or greater). The untreated black cotton soil, with a CBR of less than 2%, was unsuitable as a subgrade. The CKD-SCBA composite improved the soil’s CBR to 16.43%, upgrading it to an S4 subgrade, which can reduce the pavement thickness and associated costs. Other enhancements included an increase in UCS from 97.5 kPa to 555.81 kPa, a reduction in the FSI from 86% to 45%, and a reduction in Plasticity Index (PI) from 26.18% to 15.26%.